Behavior-Based Safety Applied to the Mining Sector - Silva-Canlla, Rhusber; Vela-Alfaro, Leonela; Licapa-Redolfo, Gladys S. (LACCEI, 2023)
In the present investigation, behavior-based safety (SBC) is evaluated in five cases of mining companies in Peru, which present difficulties with their safety systems, which is reflected in the number of registered accidents and their high rate. of accident rate. The methodology used is the analysis of the SBC as the ideology, development and its components in each specific case. In addition, two real cases were explored and the impact that the implementation of Behavior-Based Security had on their operations and especially their security, determining the efficiency of this system, reaching the conclusion that security not only consists of following a series of rules or safety regulations, this goes further, even taking into account the psychological factor of the workers, in the sense of ensuring not only their physical safety, but also their mental safety, because mining workers are the ones who are most exposed to work stress and other damages such as depression and anxiety, this due to social isolation and the formats of working hours. In this sense, Behavior-Based Safety is the best alternative to improve the safety of the five companies with the most cases of accidents in the last ten years in Peru, since it meets all the parameters and requirements required by safety. in mining.